Perlindungan Hukum Bagi Anak Pasca Putusan Dispensasi Kawin yang Ditolak Berdasarkan Peraturan Perundang-Undangan Terkait - Hani Suriyani; Nyulistiowati Suryanti; Hazar Kusmayanti (Hakim, 2023)
The latest minimum age of marriage has been stipulated in Article 7 paragraph (1) of the Marriage Law, namely a man and a woman aged 19 years, but if there are urgent circumstances that cause a person to have to carry out a minor marriage, the male parent and/or the woman's parents can request a marriage dispensation application to the court. The object of study in this study is the rejection of marriage dispensation at the Soreang Class I B Religious Court Number 163/Pdt.P/2023 and Number 5/Pdt.P/2023. The purpose of this study is to find out and formulate how the legal protection for the children of the Petitioners after the rejection of marriage dispensation by the judge. Child protection is all activities to guarantee, protect children and their rights in order to live, grow and develop, participate optimally in accordance with human dignity and dignity and get protection from violence and discrimination. The approach method used in this study is normative juridical with analytical descriptive research specifications. This research uses secondary data obtained from the results of literature studies as the main data and also uses primary data obtained through legal materials, namely related laws and regulations as a complement by using data collection techniques by means of document studies and interviews, as well as data analysis using qualitative data analysis methods. The rights of children in terms of jni concern the basic needs that should be obtained by children to ensure survival, growth, and, development as well as protection from all forms of mistreatment, exploitation and neglect of children, both including civil, economic, social and cultural rights. Child protection efforts are divided into two, namely preventive efforts and repressive efforts. Child protection efforts that the author will discuss in this paper are repressive child protection efforts, namely in the form of restoring children's condition both psychologically and physically after the rejection of marriage dispensation by the judge.